A study of maternal and perinatal outcome in cases of HELLP and partial HELLP syndrome - Durugkar, Kanchan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The HELLP syndrome is a serious complication in pregnancy characterized by haemolysis, elevated liver enzymes and low platelet count occurring in 0.5 to 0.9% of all pregnancies and in 10-20% of cases with severe preeclampsia. The objective of the present prospective study is to study on incidence, diagnosis, and variable presentations of HELLP syndrome in preeclampsia to analyse the severity and complications, as it is associated with maternal, perinatal morbidity and mortality. HELLP syndrome is difficult to diagnose when it presents with atypical clinical features. Methods: In the prospective study of 300 admitted cases with more than 20 weeks of gestation, were having preeclampsia. The selected cases were analyzed clinically with relevant history, clinical data and detailed laboratory investigations made for better analyses of complications and outcome in HELLP syndrome. Results: Under further clinical diagnosis of 300 cases of preeclampsia, 34 cases (11.33%) were of HELLP Syndrome and 44 (14.66%) cases were of partial HELLP syndrome. The present study shows 2.9% maternal mortality in HELLP and 4.5% in partial HELLP syndrome. Perinatal mortality was 17.6% with HELLP and 25% with partial HELLP. Conclusions: The diagnosis of HELLP syndrome has been made as a severe variant and complication of severe preeclampsia and eclampsia. It needs early diagnosis, timely intervention to arrest further progress and complications like multi organ dysfunction, renal failure, DIC, abruption etc and to improve maternal and perinatal outcome.